Pengaruh Pendidikan Agama Islam Terhadap Kesejahteraan Psikologis Siswa - Rohmah, Ucik Saidatur (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Islamic Religious Education (PAI) plays a significant role in influencing students' psychological well-being and shaping character, morality and religious identity. Research shows that the level of religiosity and understanding of Islamic teachings is positively correlated with psychological well-being. PAI teachers have an important role as role models in shaping student identity. This literature study uses literature research methods by collecting data from various sources. The research results highlight the role of PAI in shaping student identity through learning Islamic teachings and teacher example. PAI also contributes to character formation, attitudes of tolerance, and appreciation for differences. The correlation between Islamic religious morality and students' psychological well-being emphasizes the importance of religious aspects in the formation of students' identity and well-being. Islamic Religious Education creates a balance between academic achievement and psychological well-being by helping students overcome stress, increase optimism, develop social skills, and improve the quality of learning. In conclusion, PAI is not only a religious subject, but also the main pillar in forming quality individuals with good psychological well-being. The role of PAI teachers and further support is needed to maximize the positive impact of PAI in achieving the goals of character formation and student welfare.